KORELASI PENGGUNAAN MEDIA GAMBAR IPS DENGAN HASIL BELAJAR SISWA SDN 10 SIMPANG DUA KETAPANG - Asen, Antonius; Marli, Suhardi; ., Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
This study aims to describe how big media uses image correlation in social studies learning with learning outcomes fifth grade students of SDN 10 Simpang Dua Ketapang district of West Kalimantan Province. The method used is descriptive research form association studies. The sample in this study was 20 students. Use of media images in social studies learning in SDN 10 Simpang Dua Ketapang by 2.98 which is quite, while the learning outcomes of students in fifth grade social studies lesson SDN 10 Simpang Dua Ketapang showed an average of 62.5 study results are considered sufficient. Results of statistical calculations know that, between the use of media with images of student learning outcomes is positive with regard to the count r obtained at 0.876 with a range of numbers is between 0.80 to 1.000 means that there is a significant correlation between the use of media images in teaching social studies in SDN 10 Simpang Dua Ketapang included in the category of very strong. Kayword: Media Images, Student Learning Outcomes, Social Studies Learning Abstrak: Penelitian ini bertujuan untuk mendeskripsikan seberapa besar korelasi penggunaan media gambar dalam pembelajaran IPS dengan hasil belajar siswa kelas V SDN 10 Simpang Dua Kabupaten Ketapang Provinsi Kalimantan Barat. Metode penelitian yang digunakan adalah deskriptif dengan bentuk penelitian studi hubungan. Sampel dalam penelitian ini adalah 20 siswa. Penggunaan media gambar dalam pembelajaran IPS di SDN 10 Simpang Dua Kabupaten Ketapang sebesar 2,98 yang tergolong cukup, sedangkan hasil belajar siswa pada pembelajaran IPS kelas V SDN 10 Simpang Dua Kabupaten Ketapang menunjukan rata-rata hasil belajar sebesar 62,5 yang tergolong cukup. Hasil dari perhitungan statistik ketahui bahwa, antara penggunaan media gambar dengan hasil belajar siswa bernilai positif dengan memperhatikan besarnya r hitung yang diperoleh sebesar 0,876 dengan rentang angka terletak diantara 0,80 1,000 berarti ada korelasi yang signifikan antara penggunaan media gambar dalam pembelajaran IPS di SDN 10 Simpang Dua Kabupaten Ketapang termasuk dalam kategori sangat kuat. Kata Kunci : Media Gambar, Hasil Belajar Siswa, Pembelajaran IPS